Analysing the Placement Test Questions at University in Egypt Based on the Common European Framework of Reference for Languages (CEFR) - Miqdarul Khoir Syarofit; Hanik Mahliatussikah; Muhammad Alfan; Salma, Ria Fauziah (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2025)
The Taḥdīd al-Mustawa (proficiency level determination) test is a critical gateway for international students at Al-Azhar University, Egypt, making its psychometric quality paramount. This study aimed to provide a comprehensive quality analysis of this high-stakes test by evaluating its validity, reliability, difficulty level, and discriminant power. A quantitative descriptive-analytical design was employed, using Classical Test Theory (CTT) to analyze the 70 multiple-choice items from the 2025 placement test. The results revealed a robust instrument: 85.7% of items demonstrated good to high validity, and the test achieved excellent internal consistency reliability with a Cronbach's alpha of 0.89. Furthermore, the test exhibited an ideal difficulty distribution, with 65.7% of items categorized as moderate. The discriminant power was also highly satisfactory, with 78.6% of items effectively differentiating between high- and low-proficiency students. This study concludes that the test is a valid and reliable instrument, although data-driven recommendations are provided for revising a small subset of underperforming items.